A DISCUSSION ON CONTEMPORARY EDUCATION AT THE CROSSROADS OF DISCIPLINARY AND BIOPOLITICAL POWER - Yunus Emre ÖMÜR (Fırat University, 2021)
The discourses that shape the debate on education today emerge in the mediation of dominant power relations. Hence, conducting any discussion of education necessitates discussing education in the context of power relations and placing it on a political basis. Because knowing the types of thinking that support institutions is as important as knowing the institutions themselves. This approach will contribute to overcoming the intellectual barriers created by treating education and training as if it were just a natural reality of the state or government. In other words, it is necessary to examine in which power relations the dominant discourses of today's education emerge. In this study, the issue of education is discussed in the context of disciplinary and supervisory power relations and how education is articulated with the process of subjectivity fabrication as a human capital investment in the neoliberal age. This discussion, which is carried out on the basis of Michel Foucault's concept of power, handles the supervisory and disciplinary modes of power in relation to education. In line with this purpose, first of all, what disciplinary power is discussed, and it is tried to reveal the qualities of schools as a disciplinary institution. Afterward, by mentioning the differences between biopolitical power, which is the supervisory mode of power, and disciplinary power, it is discussed how education is articulated to the fabrication of subjectivity as a neoliberal discourse of human capital. Consequently, compulsory education plays an active role in the production of the neoliberal subject as an institution at the intersection of both disciplinary power and supervisory power.